Preparation and characterization of YMnO3 thin films by metal–organic decomposition. (1st March 2023) - Watanabe, Kanata; Nishikawa, Masami; Sakaguchi, Hotaka; Veis, Martin; Ishibashi, Takayuki
Abstract: Hexagonal rare-earth manganese oxide YMnO3 thin films were prepared on yttria-stabilized zirconia (111) substrates by metal organic decomposition method. The crystallinity and morphology of YMnO3 thin films crystallized at various temperatures were examined by X-ray diffraction and atomic force microscopy measurements, respectively. Single phase YMnO3 was obtained for the sample prepared by annealing temperatures of 950 °C. AFM analysis revealed that a smooth surface with a roughness of 0.15 nm was achieved for YMnO3 thin film annealed at 950 °C and 1000 °C, while three-dimensional growth for other samples prepared at 750–900 °C, 1050 °C, and 1100 °C. A narrow band at 1.6 eV and a broad band at 5 eV due to electronic transitions in the manganese and oxygen bands were observed in an absorption spectrum.